A pilot study on platelet response to aspirin with whole blood platelet aggregation methods in stable coronary artery disease patients - Sanada, Abu Bakar (2008)
Aspirin is an anti-platelet agent used to prevent thrombo-embolic complications related to coronary artery disease. It is currently the most cost effective drug for the secondary prevention of coronary artery disease, but treatment failures are relatively common. The tenn aspirin resistance has been used to describe not only an absence of the expected phannacologic effects of aspirin on platelets but also poor clinical outcomes, such as recurrent vascular events and sudden death. By studying the platelet function, the anti platelet effects of aspirin can be assessed. Traditional platelet function study as a gold standard was done by platelet aggregation method using PRP specimen. However, PRP preparation was laborious, need higher specimen volume and is non-physiological. This test however has established criteria for classification of aspirin sensitive and aspirin resistance status. Using whole blood specimen is less laborious; less specimen volume is needed and more physiological. The aims of this study were: 1) to determine the agreement between PRP and whole blood specimen using same platelet analyzer in stable coronary artery disease patients; 2) to compare the results between 2 whole blood methods using different platelet analyzer and 3) to study the laboratory and clinical characteristics of the patients classified as aspirin sensitive and aspirin resistance group. A cross sectional study of stable coronary artery disease patients attending Cardiology Clinic at HUSM was conducted in year 2006. Forty patients were analyzed using whole blood by Chronolog analyzer. Among these patients, they were also analyzed by 2 other different methods. Nine patients were analyzed using PRP by same Chronolog analyzer. Another 25 patients were analyzed using whole blood by Multiplate platelet function analyzer (new automated analyzer). Abnormal platelet aggregation induced by platelet agonist (AA and ADP) is expected in patients responding to aspirin( aspirin sensitive).The prevalence of aspirin resistance was 10% and 20% with Chronolog analyzer and Multiplate analyzer respectively. In this preliminary study, we found that both PRP and WB samples using Chronolog platelet aggregometer have a good agreement to categorize resistance status to aspirin. Higher detection of platelet resistance was seen by Multiplate analyzer than whole blood Chronolog platelet analyzer. There were no significant differences with regard to age, race, sex, smoking, hyperlipidemia, diabetes mellitus, hypertension and platelet count between aspirin sensitive and aspirin resistance groups. For laboratory parameters, abnormal ATP released with AA and ristocetin aggregation showed significant difference between aspirin resistance and responder group.